"Influence Of Nano Lubrication In Machining Operations - A Review". (2018) - Ajithkumar, J.P.; Anthony Xavior, M.
Abstract: Controlling the usage of cutting fluids and lubricants are more significant in reducing the machining cost, environmental conservation and the protection of operator health conditions. To enhance the performance of cutting fluids, nano-lubricants have been introduced in various propositions for different machining processes. Nano lubricants are the mixture of nano particles, dispersant and cutting fluids. It is attributed to the rolling or sliding or filming of nano particles in the tool-work-piece interface. Heat generation due to the high frictional force leads to thermal damage of the work piece as well as tool material. It is observed that the machining cost directly depends on the metal removal rate. Inclusion of nano particles in the lubricants improves the wettability, lubricant properties and heat transfer efficiency, thereby increasing the tool life and surface finish. Currently, application of Nano Fluid Minimum Quantity Lubrication (NFMQL) technique is emerging due to the excellent improvement in machining outputs, reduce tool wear and improve the surface quality when compared with the other lubrication techniques. This review focuses on the influence of nano lubrication on tool wear, surface roughness, heat generation and cutting forces. In addition, the type, size and concentration of nano particles also discussed. From the literatures, it has been identified that the application of nano lubrication with more nano particles concentration enhances the surface finish and reduces tool wear, heat generation, cutting force and power requirement when compared with dry and other conventional lubrication. The comprehensive review on the use of nano lubrication as found in different literatures and identification of effective methodologies to improve the behaviour of nano particles in a machining process are presented in this paper.